Optimizing inventory management in the textile industry: a comprehensive evaluation of UHF-RFID technology integration - Darmawi, Ahmad; Istikowati, Rita; Astrini, Galuh Yuli (Institute of Advanced Engineering and Science, 2025)
The integration of ultra-high frequency radio frequency identification (UHF RFID) technology presents a transformative solution to inventory management challenges in the textile industry. This study examines the implementation of a web-based inventory management system incorporating UHF-RFID technology at AK-Tekstil Solo, focusing on its impact on inventory accuracy, operational efficiency, and product traceability. The developed system facilitates real-time tracking of yarn products, streamlines inventory audits, and minimizes manual errors, resulting in substantial improvements in inventory control and warehouse management processes. By enabling automated data capture and tracking, UHF-RFID technology supports the transition to smart warehousing by providing real-time insights into inventory movements. The findings demonstrate that UHF-RFID technology offers significant advantages, including enhanced inventory visibility, cost savings, and improved customer satisfaction through better product availability. Despite potential implementation challenges, the study shows that the long-term benefits of UHF-RFID integration outweigh the initial costs, proving it to be an effective solution for optimizing inventory management in the textile industry. Future research may explore the integration of complementary technologies such as the internet of things (IoT) and artificial intelligence (AI) to further enhance UHF-RFID enabled inventory management systems.